Pejabat HEP Anjur Kursus Training of Trainer - Safei, Su'aidi (KUTKM, 2003)
Training of Trainers Course was jointly organized by the Student Affairs Office, KUTKM and National Civics Bureau (BTN). It aimed to provide understanding and guidance to the participants prior to be commissioned by BTN as speakers and certified facilitators.